Influence of Alternation of Sulfate Attack and Freeze-Thaw on Microstructure of Concrete - Huaquan Yang; Xiaoming Shen; Meijuan Rao; Xiang Li; Xiaodong Wang (Advances in Materials Science and Engineering)
The effects of sulfate attack and freeze-thaw alternation on the concrete microstructure were systemically investigated by advanced test methods such as water absorption method, air void analysis, XRD, and SEM. The experimental results indicated that freeze-thaw damage is the major effective factor in the sulfate attack and freeze-thaw alternation test. In the alternation test, average aperture of capillary pores of specimens was smaller, pores uniformity was better, and water absorption rate was lower than those specimens used in the single freeze-thaw damage test. The average aperture and uniformity of pores could be improved by adding fly ash and slag. Damage was accumulated in many cycles of freeze-thaw and microcracks increased during the test. At the same time, the hydration products of the concrete developed into expansive gypsum, AFt, and TSA without any strength during sulfate attack. The results of the microstructure analysis form XRD and SEM are in accordance with that of AFt, about 3 μm length, around which other hydration products decomposed by C-S-H after sulfate attack resulted in loss of concrete strength.